(untitled) (Annual of the Faculty of Philosophy in Skopje, 2020)
In latest years, the Dark web has converted to one of the most debated themes in cyber security circles. Recent academic analyses and media articles tend to focus how the anonymous nature of the Darknet is used to enable criminal activities. This article analyses and underlines the major roles played by the Dark Web as a market; as a communication platform; as an enabler of cybercrime; as an enabler of anonymous financial transactions and as a proxy to a surface web. Precisely, it draw attention to the ‘black market’ of the Internet–the dark web that represents such a hidden space, being the largest deployed anonymity network. This success is supported by numerous features that are imbedded in the high-tech structure of the Dark web, for instance, secrecy, anonymity and the usage of cryptocurrencies. The distinctive environment of Dark Net markets as extremely anonymous and secretive, as well as reliable, makes them an ultimate test case for the unrestrained online marketplace.